تأثير إستراتيجية تبادل الأدوار المقرون بأسلوب التمرين المتغير في تعلم و إكتساب بعض المهارات الحركية بكرة القدم - عزيز، إبراهيم محمد; حسن، آريان بهاء الدين; قادر، حتم صابر (جامعة صلاح الدين, 2014)
إن استراتيجية تبادل الأدوار في تعلم وتدريس التربية الرياضية تساعد الطلاب على تحقيق أهدافها وتعتبر تلك الأدوار مهمة لجودة التعلم ويشعر أفراد المجموعة التعليمية التعاونية بمسؤولية شخصية تجاه المشاركة وتضيف إلى دافعية الطلاب مفهوم الالتزام أو الواجب، هذا بالإضافة إلى أنها تزود الطلاب بالخبرات التعليمية ذات الجودة العالية التي من شأنها أن تزيد من تعلمهم وتكيفهم الاجتماعي في المجتمع. The strategy of the exchange of roles in learning and teaching sports to help students achieve their goals, and are those roles important to know the quality and feel of the group educational cooperative responsibility for personal toward participation and add to the motivation of the students the concept of obligation or duty, in addition to that they provide students with experience teaching withhigh quality that would increase their learning and social adaptation in society. The research aims to found: Which is the best in terms of the effectiveness of the use of the exchange of roles strategy coupled with exercise variable manner and traditional (approach) and their impact in the acquisition of some motor skills in football. The researchers used experimental method for suitability with the nature of the research, and the research community has been selected in a deliberate second phase students in the Faculty of Physical Education at the University of Salahaddin in Erbil for the academic year (2012-2013) at (4) people, and the sample Vtm selected randomly Statistics (lottery) as two divisions were selected, (Division b) and (c Division) Division has been adopted (b) of (14) as a student pilot, and Division (c) of (14) students as a control group . The researcher concluded the following: - The use of the exchange of roles strategy coupled with exercise variable manner as well as the traditional method (used) with a positive impact and to varying degrees in learning some of the motor skills to football. - The superiority of the experimental group over the control group in the skill tests under study football.
Keywords: العملية التعليمية -- تدريس التربية الرياضية -- طلاب الجامعات -- كرة القدم